Efeito nefrotóxico direto induzido pela fração L-aminoácido oxidase isolada do veneno da serpente Bothrops leucurus - Morais, Isabel Cristina Oliveira de (2015)
The pit viper Bothrops leucurus (White-tailed-jararaca) is a poisonous snake habituating area in the northeast of Brazil. The biological effects due envenomation have similar profile than those observed with other Bothrops, such as important severe local and systemic effects such as Acute Renal Failure (ARF). Bothrops leucurus venom induces nephrotoxicity in the isolated perfused kidney of rats associated with cytotoxicity against renal tubular epithelia cells. In this study, it was evaluated the direct nefrotoxicity of L-aminoacid oxidase isolated of B. leucurus venom (LAAO-Bl) on renal epithelial cells (MDCK and HK2) and their potential nephrotoxic in isolated rat kidney. In these cells treated with LAAO-Bl, 1.56 – 100 µg/mL for 12 h, there was a decrease in their viability in a concentration-dependent manner after 12 hours of treatment. In MDCK cells LDH release was not observed after 12 h of LAAO-Bl exposure while LAAO-Bl induced membrane rupture in HK-2 cells at the highest concentrations studied when compared with untreated cells. In MDCK cells, LAAO-Bl significantly increased the percentage of early apoptotic (Annexin-V+, PI-), necrotic (Annexin-V-, PI+) and secondary necrotic cells (Annexin-V+, PI+) when compared with control untreated cells. In HK-2 cells LAAO-Bl induced an increase in necrotic (PI+ cells) and secondary necrotic cells (Annexin-V+, PI+) in a concentration-dependent manner. MDCK apoptosis induction was accompanied with Ca2+ release from the endoplasmic reticulum, reactive oxygen species (ROS) generation, mitochondria dysfunction with enhanced expression of Bax protein levels. LAAO-Bl induced caspase-3 and caspase-7 activation in both cell lines. LAAO-Bl (10 µg/mL) exerts significant effects on the isolated kidney perfusion increasing perfusion pressure and urinary flow and decreasing the glomerular filtration rate and sodium, potassium and chloride tubular transport. Taken together our results suggest that LAAO-Bl contributes for the nephrotoxicity observed in the envenomation by Bothrops leucurus. Moreover, the cytotoxic of LAAO-Bl to renal epithelial cells might be responsible, least in part for the nephrotoxicity observed in isolated kidney.